LAICE CubeSat mission for gravity wave studies. Issue 7 (1st October 2015) - Westerhoff, John; Earle, Gregory; Bishop, Rebecca; Swenson, Gary R.; Vadas, Sharon; Clemmons, James; Davidson, Ryan; Fanelli, Lucy; Fish, Chad; Garg, Vidur; Ghosh, Alex; Jagannatha, Bindu B.; et al.
<x xml:space="preserve">Abstract</x> Highlights LAICE CubeSat has been designed to address fundamental questions of atmospheric coupling. LAICE will focus on studying the interaction of weather-sourced gravity waves with the MLTI region. LAICE will combine remote and in-situ observations of ion and neutral variations in the MLTI region.